The Involvement of Oxidative Stress in Psoriasis: A Systematic Review - Elena-Codruța Dobrică; Matei-Alexandru Cozma; Mihnea-Alexandru Găman; Vlad-Mihai Voiculescu; Amelia Maria Găman (MDPI AG, 2022)
Psoriasis is a chronic, immune-mediated inflammatory dermatosis characterized by the appearance of erythematous plaques, covered by white scales, occasionally pruritogenic, and distributed mainly on the extensor areas. Oxidative stress is defined as an imbalance or a transient or chronic increase in the levels of free oxygen/nitrogen radicals, either as a result of the exaggerated elevation in their production or the decrease in their ability to be eliminated by antioxidant systems. Although the pathogenesis of psoriasis remains far from elucidated, there are studies that delineate an involvement of oxidative stress in this skin disorder. Thus, a systematic search was computed in PubMed/Medline, Web of Science and SCOPUS and, in total, 1293 potentially eligible articles exploring this research question were detected. Following the removal of duplicates and the exclusion of irrelevant manuscripts based on the screening of their titles and abstracts (n = 995), 298 original articles were selected for full-text review. Finally, after we applied the exclusion and inclusion criteria, 79 original articles were included in this systematic review. Overall, the data analyzed in this systematic review point out that oxidative stress markers are elevated in psoriasis and share an association with the duration and severity of the disease. The concentrations of these biomarkers are impacted on by anti-psoriasis therapy. In addition, the crosstalk between psoriasis and oxidative stress is influenced by several polymorphisms that arise in genes encoding markers or enzymes related to the redox balance. Although the involvement of oxidative stress in psoriasis remains undisputable, future research is needed to explore the utility of assessing circulating serum, plasma, urinary and/or skin biomarkers of oxidative stress and of studying polymorphisms in genes regulating the redox balance, as well as how can these findings be translated into the management of psoriasis, as well in understanding its pathogenesis and evolution.